Safety and Feasibility of Ultrasound-Guided Access for Coronary Interventions through Distal Left Radial Route. (25th March 2022) - Ghose, Tapan; Kachru, Ranjan; Dey, Jaideep; Khan, Wasi Ullah; Sud, Ratna; Jabeen, Suraiya; Husain, Shahnawaz; Pant, Aparna
Abstract : Aims . Left distal transradial arterial approach (ldTRA) is a new interventional route that spares right radial artery (RRA) for use in haemodialysis and as bypass graft. V asant K unj L eft dI stal T ransradial ArtE ry approach (VKLITE) study aimed to assess the feasibility and safety of ldTRA access during coronary angiography (CAG) and percutaneous coronary intervention (PCI). Methods and Results . Between April 2018 and June 2020, 108 patients were enrolled and underwent CAG ± PCI via ultrasound guided ldTRA. Arterial puncture, CAG, and PCI were successful in 96.3% (104/108), 92.1% (93/101), and 94.1% (32/34) patients, respectively. Access site crossover rate was 14/108 (13.0%). Mean puncture, procedure, and haemostasis time (minutes) were 6.7 ± 7.1, 55.7 ± 32.8, and 23.1 ± 11.9. Median total fluoroscopic time was 6.6 minutes (IQR-14.2), and median total radiation dose was 39.2 Gy-cm 2 (IQR-97.0). Local haematoma occurred in 11 patients (10.2%) with major haematoma in 1.9%, all recovering within three weeks. Mean pain score was 2.4 ± 2.3, and patient satisfaction score was 9.0 ± 1.3. LdTRA access compared with RRA access ( n = 121) showed significantly increased mean procedure time (55.7 ± 32.8 vs. 43.9 ± 26.0 minutes, p = 0.01) and median total fluoroscopic time (6.6 [IQR-14.2] vs. 4.7 [IQR-8.2] minutes, p = 0.02), with similar median total radiation dose (39.2 [IQR-97.0] vs. 43.8 [IQR-54.5] Gy-cm 2, p = 0.56). No radial artery loss, dissection, pseudoaneurysm, arteriovenous fistula, or nerve injury was noted. Conclusions . LdTRA access is feasible with few complications during CAG/PCI. Patient comfort and satisfaction makes it a desirable route for coronary interventions.